2020
DOI: 10.3390/en13061338
|View full text |Cite
|
Sign up to set email alerts
|

Determination of NMR T2 Cutoff and CT Scanning for Pore Structure Evaluation in Mixed Siliciclastic–Carbonate Rocks before and after Acidification

Abstract: Nuclear magnetic resonance (NMR) is used widely to characterize petrophysical properties of siliciclastic and carbonate rocks but rarely to study those of mixed siliciclastic–carbonate rocks. In this study, 13 different core samples and eight acidified core samples selected amongst those 13 from the Paleogene Shahejie Formation in Southern Laizhouwan Sag, Bohai Bay Basin, were tested by scanning electron microscopy (SEM), micro-nano-computed tomography (CT), and NMR. SEM and CT results revealed a complex pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Its right peak position is below 2 μm in most cases; GFC pores are narrow, mostly unimodal of small pores or bimodal showing a distinct smaller slanting degrees, and the left peak position is mostly below 0.01 μm, the largest pore of some samples is less than 0.1 μm, and some have a larger right peak position, which may be related to the microcracks generated at the weak point of the gravel edge cementation. 49 …”
Section: Resultsmentioning
confidence: 99%
“…Its right peak position is below 2 μm in most cases; GFC pores are narrow, mostly unimodal of small pores or bimodal showing a distinct smaller slanting degrees, and the left peak position is mostly below 0.01 μm, the largest pore of some samples is less than 0.1 μm, and some have a larger right peak position, which may be related to the microcracks generated at the weak point of the gravel edge cementation. 49 …”
Section: Resultsmentioning
confidence: 99%
“…Chips are broken from the center of the plug for SEM imaging. The core material is maintained at 15 °C during SEM imaging 12 . Presence of wax is confirmed by photomicrographs.…”
Section: Properties Of Crude Oil In the Experimentsmentioning
confidence: 99%
“…Well drilling investigations have revealed that the Neogene Guantao Formation, Palaeogene Shahejie Formation and Mesozoic strata all have strong oil and gas shows 32 . This area is in a low-exploration area and has great exploration potential 33 . Among these strata, the Mesozoic mainly developed the Cretaceous Yixian Formation and Jurassic Lanqi Formation volcanic strata with complex lithologies, which are the main target strata of this study [34][35][36] (Fig.…”
Section: Geological Backgroundmentioning
confidence: 99%